The effect of coloured LED light treatments on the biosynthesis of flavonoids in woodland strawberry (Fragaria vesca L.) originating from different latitudes - Omole, Florence Omowumi (UiT Norges arktiske universitet, 2019)
Flavonoids are a group of phenolic compounds produced in plants. They have many biological functions in plants and also beneficial bioactivities in human’s health. Light quality is one of the major environmental factors regulating the accumulation of flavonoids in plants. Understanding plants accumulation of secondary metabolites in response to light qualities is important in order to optimize plants quality and cultivation conditions. The biosynthesis of flavonoids is well understood and the structural genes of the pathway have been characterized from many plant species, including Fragaria spp. The MYB-R2R3 transcription factors play significant roles in regulating the flavonoid biosynthesis genes. FvMYB10 acts as a positive regulator of late anthocyanin biosynthesis gene in both leaves and third ripe stage berries, FvMYB1 also acts as a repressor in the early fruit developmental stages. However, in leaf tissues, it interacts with FvMYB10 to positively regulate flavonoid pathway genes. In the present study, an experiment was carried out to study the effect of spectral light qualities (red, blue, far-red, white fluorescent light as control) on F. vesca clones from a different latitudinal origin; Italy, South Finland and North Norway, two separate clones from each origin. The results showed that red and blue LED lights had a prominent effect on the total anthocyanin accumulations and the related gene expression in all clones, although the effects vary between leaves and fruits. Also, F. vesca clones of different origins responded differently to the LED light treatments. The leaves and early stage fruits of the Italian clones responded most to blue light, whereas the leaves and the early stage fruits of the Finnish and North Norwegian clones responded most to red light. Interestingly, a shift in this pattern was detected at the end of fruit ripening, when the Italia clones responded more to red light, similarly to the Finnish clones, and the Norwegian clones responded more to blue light. Therefore, the results of ...